جمـــاليــات التـَّــوازي التــَّـركيبـــي التَّام ( الربــط بالــواو نمـوذجــاً ) - بابو, غياث (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
تُعدُّ العناصر المُشكِّلة التَّركيب النَّحوي واحدةً من أهمِّ البنى اللغوية لخطاب التَّوازي في النسق اللغوي: الشعري والنثري؛ لأنَّ التوازي مركّب من سلسلتين لغويتين متواليتين، أو أكثر لنظام نحوي وصرفي واحد . فالتوازي شكل من أشكال التنظيم النّحوي، يتمثَّل في تقسيم النَّص، وتقطيعه إلى تراكيب وعناصر متساوية، تعطي بعداً إيقاعيّاً منتظماً، يتجلَّى في طول النغمة وقصرها، سواء أكان التوازي تامّاً، أم جزئياً، مقطَّعاً تقطيعاً طويلاً، أم قصيراً بوساطة الواو الرابطة . وهذا النّمط من الخطاب اللغوي الذي يقطّع النَّصَّ اللغوي تقطيعاً لغوياً متساوياً، يكسب التركيب انسجاماً، وإيقاعأ لايتوافران في أيِّ نصٍّ آخر . Indubitably, elements constituting the syntactic structure are one of the significant linguistic features of the symmetrical discourse in the linguistic order whether poetry or prose; since the symmetry discourse consists of two, or more, adjacent linguistic series. However, the symmetrical discourse is one form of syntactic arrangements, as appears in organizing the text, and dividing it into similar constituents that soon bring forward a recognizable rhythmical dimension, which becomes clear in how long or short the tone is, whether this symmetrical discourse is full or partial, divided into longer stretches, or shorter ones interconnected by the conjunction 'and'. No doubt that such a type of linguistic discourse, which divides the text into similar segments, acquires it harmony and cadence apparently missing in any other linguistic structure.